Experimental Study of Influence Earning Zakat Through Z-Mart on Social Economic Conditions Mustahik - Moch. Sayyid Salsabila Madani Amir; Fery Setiawan (PT FORMOSA CENDEKIA GLOBAL, 2022)
The problem of poverty is one of the many social problems in Banten Province. One of the solutions offered in Islamic law is zakat which has a close goal of reducing the problem of poverty. Through the distribution and distribution of zakat funds in the form of productive zakat, it can affect the socio-economic conditions of mustahik. The method used in this study is a qualitative method, where the data instrument is sourced from direct interviews with BAZNAS Banten Province and mustahik recipients of Z-Mart. The results of this study are that the productive zakat strategy that is distributed through Z-Mart has an impact on mustahik, the increase in profit felt by Mrs. Nahriyah is 135% per year or 19.6% per month and Mrs. Juhenah is 148% per year or 20.7 % per month compared to before receiving assistance. The conclusion of this study is the distribution pattern of productive zakat through Z-Mart carried out by BAZNAS Banten Province is in the form of capital in the form of procurement of non-contracted merchandise by qardhul hasan contract or interest-free borrowing.